The role of F18-FDG PET/CT in predicting secondary optimal de-bulking in patients with recurrent ovarian cancer. (December 2017) - Amit, Amnon; Hodes, Adina; Lavie, Ofer; Keidar, Zohar; Matanes, Emad; Lowenstein, Lior
Abstract: Background and objectives: The decision to perform secondary cytoreductive surgery for recurrent ovarian cancer is generally determined by clinical criteria. The aim of this study was to assess the predictive capability of FDG-PET/CT in identifying patients for whom secondary optimal debulking can be obtained. Methods: We reviewed the records of all women with suspected recurrent ovarian cancer (CA-125 levels >35 U/ml and/or clinical symptoms), at two medical centers, between January 2004 and December 2013. Patients in whom CT scans were negative, indeterminate or indicative of localized disease, were referred for preoperative FDG-PET/CT study. We analyzed the outcomes of those who subsequently underwent cytoreductive surgery. Results: Of 282 women with suspected recurrent ovarian cancer, 48 underwent FDG-PET/CT. The 24 for whom localized disease was detected on PET/CT, subsequently underwent secondary debulking surgery. Patients with PET/CT evidence of multifocal recurrent sites were referred for chemotherapy. Tumor debulking was optimal in 20 patients, and suboptimal in 4. The positive predictive value of PET/CT for optimal debulking was 83.3%. Conclusions: The findings extend prior reports on the role of FDG-PET/CT in the management of recurrent ovarian cancer, to the prediction of secondary optimal debulking. Future studies should aim to investigate the impact on survival.